L’atlas électronique du Minas Gerais - Louise Bruno (Cahiers des Amériques Latines)
This study contrasting three rural Mexican organizations shows how each one reconciles the demands of democracy with the requirements of accession. The rules and their interpretation are subtly accompanied by informal activities which, together, designate in advance the future national leader. Faced with the uncertainty of free elections, a single candidate is often preferred. Beyond the action programs and declarations of principles, the control of power taking is a key element in the understanding the functioning of a rural organization.